Genome analysis of the candidate phylum MBNT15 bacterium from a boreal peatland predicted its respiratory versatility and dissimilatory iron metabolism - Begmatov, Shahjahon; Beletsky, Alexey V.; Dedysh, Svetlana N.; Mardanov, Andrey V.; Ravin, Nikolai V. (Frontiers in Microbiology, 2022)
Uncultured bacteria of the candidate phylum MBNT15, distantly related to Desulfobacterota, have been identified in a broad range of mostly organic-rich aquatic environments. We assembled a near-complete genome of a member of MBNT15 from a boreal peatland metagenome and used genomic data to analyze the metabolic pathways of this bacterium and its ecological role. This bacterium, designated SHF-111, was predicted to be rod shaped, it lacks flagellar machinery but twitching motility is encoded. Genome-based phylogenetic analysis supported the phylum level classification of the MBNT15 lineage. Genome annotation and metabolic reconstruction revealed the presence of the Embden-Meyerhof, Entner-Doudoroff and pentose phosphate pathways, as well as the complete TCA cycle, and suggested a facultatively anaerobic chemoheterotrophic lifestyle with the ability to ferment peptides, amino acids, fatty acids and simple sugars, and completely oxidize these substrates through aerobic and anaerobic respiration. The SHF-111 genome encodes multiple multiheme c-type cytochromes that probably enable dissimilatory iron reduction. Consistently, the relative abundance of MBNT15 in peatlands positively correlated with iron concentration. Apparently, in the wetland ecosystem, MBNT15 representatives play the role of scavengers, carrying out the complete mineralization of low molecular weight organic substances formed as a result of microbial degradation of complex polymeric substrates. Comparative genome analysis of the MBNT15 phylum revealed that vast majority of its members are capable of aerobic respiration and dissimilatory iron reduction and some species also can reduce sulfur and nitrogen compounds, but not sulfate. Based on phylogenetic and genomic analyses, the novel bacterium is proposed to be classified as Candidatus Deferrimicrobium borealis, within a candidate phylum Deferrimicrobiota.